State Responses to Minority Religions - Kirkham, David M. (Farnham Ashgate Publishing Ltd, 2013)
This book explores state responses to minority religions in four parts. The first chapter provides a legal and normative overview of the variety of responses available to states. Part II looks at Islamic majority countries, and part III focuses on Western Europe, paying particular attention to the rise in the twentieth century of the 'sect' and exploration of the European Court of Human Rights. Part IV shifts to the east, specifically analysing Russia and the Baltics. The book concludes with a look at state responses from non-European democracies, including different perspectives on the Canadi
13 With Fear and Favour: Minority Religions and the Post-Soviet Russian State14 China's Responses to Minority Religions; Part V Minority Religions in Non-European Democracies: Canadian and South African Models; 15 Expanding the Scope of Regulation: Some Reflections on Religious Minoritiesin Canada; 16 The Constitutional Protection of Religious Practices in Canada; 17 Religious Minorities' Right to Self-Determination; Bibliography; Index
Description based upon print version of record
Online-Ausg.
Keywords: Religion and state; Electronic books; Electronic books